Desenvolvimento teórico-experimental de um modelo de turbina Tesla aplicado à geração descentralizada por fontes renováveis - Couras, Daut de Jesus Nogueira Peixoto (2009)
The current master’s dissertation treats the experimental and theoretical development of a new model of Tesla turbine, also known as disk turbine, in which the research focus was to study this propulsion device viewing its application in distributed energy generation systems from biomass renewable resources. A turbine’s prototype was developed, in laboratory scale, to determine the design parameters through the theoretical and experimental studies in order to interpret the phenomena present in the internal processes of this kind of flux machine. The research was directed toward the effect analysis of the gap between disks on the torque and the power, as a function of the flow’s fluidynamic boundary layer, correlating the flow velocity regimes with the working fluid properties. A methodology for isentropic and exergetic efficiency calculation is taken from experimental data and theoretical analyses through simulation (supported by the software ANSYS-CFX), which determines the pressure distribution profile inside the expansion chamber, characterizing flow lines and pressure gradients. Complementarily, a modal analysis of turbine’s vibration signals is performed, studying the dynamic behavior of the structure with the purposes of detecting the natural frequencies and investigating the influence of the disk’s gap on the vibration level of this device. This study points out the robustness and the operational versatility of this kind of turbine by the fact of it allows a wide rotation range and by its easy adaptation to commercial generators, suggesting its application into generation and co-generation systems for the rural area as well as for the industry.